The History and Evolution of Fitness - Ali Sevilmis; İlknur Özdemir; Jerónimo García-Fernández (Universidad de Murcia, 2023)
Mankind has always maintained the mentality of vitality since its existence. Fitness was used to survive through hunting and gathering required by living conditions in ancient times, the movement arising from competition during the cold war period was seen as a propaganda tool in certain periods, and today as a mass sport that prioritizes muscle, beauty and aesthetics used commercially. In the modern world, fitness, which is done with external appearance and aesthetic concerns, has a very old history. This article will highlight historical events and influential individuals who shaped the history of fitness, from primitive man to the founding of the modern fitness movement. For this reason, the history of fitness in the research; In societies, body culture, primitive people and fitness, before and after the industrial revolution, between certain years (1920-1990), were gathered under the titles of today's fitness. As a result, fitness, which developed as a result of physical culture in the 20th century, has a large market in the world.